The influence of ultrasonic surface rolling on the fatigue and wear properties of 23-8N engine valve steel. (August 2019) - Lai, Fuqiang; Qu, Shengguan; Lewis, Roger; Slatter, Tom; Fu, Wenlan; Li, Xiaoqiang
Highlights: 23-8N engine valve steel was treated by ultrasonic surface rolling technique. The microstructures of the modified layer were nano-scale lamellar grains. The treatment led to a reduction in surface roughness and coefficient of friction. The fatigue strength and wear resistance were increased after treatment. The cracks initiation mechanism was influenced by the residual stress in specimens. Abstract: An ultrasonic surface rolling (USR) technique was employed for the first time as a method to enhance the fatigue and wear resistance of 33Cr23Ni8Mn3N (23-8N) austenitic engine valve steel. The microstructure of the modified layer on the material surface was characterised by scanning electron microscopy (SEM) coupled with electron back scatter diffraction (EBSD) and transmission electron microscope (TEM) methods. Nanoscale lamellar grains were discovered on the top surface of the treated material, and an increase of compressive residual stress and microhardness of the surface material observed. A comparative fretting wear test and a rotating bending fatigue test were performed out to verify the surface enhancement effect. Fractured and worn faces of specimens were evaluated through utilizing SEM and energy–dispersive spectroscopy (EDS). Compared to the untreated material, the coefficient of friction of USR treated material was significantly reduced, and the wear resistance was improved. The fatigue strength of a specimen treated at 25 °C was increased from 528 MPa to 730 MPa (38.3%). At 650 °C, the fatigue strength increased from 345 MPa to 400 MPa (15.9%). The fatigue resistance extension and wear resistance improvement of treated specimen can be attributed to a combination of beneficial compressive residual stress, work hardening, and the modified microstructure with fine-grains in the surface layer, and thus demonstrates the validity of this novel technique.